LEGAL ASPECTS OF TUBERCULOSIS CARE PROVISION IN RUSSIA AT THE TURN OF THE XIX-XX CENTURIES - A. A. Chulochnikov; A. V. Basova; A. I. Zavyalov (Туберкулез и болезни лёгких, 2018)
The objective of the study: to analyze the legal regulation of tuberculosis care provision to the population ofRussia at the turn of the XIX-XX centuries.Methods. Systemic analysis of RSFSR regulations, scientific literature and archive information devoted to tuberculosis care provision during the examined period.Results. Certain problems of legal regulation in the organization of anti-tuberculosis care at the turn of the XIX-XX centuries were detected.Conclusion. The article concludes that in the 20s of the XX century in RSFSR, TB services were set up, an organization of anti-tuberculosis care was regulated by the state, social support for tuberculosis patients was guaranteed, but unfavorable social and economic conditions existing in the country did not allow stopping the transmission of tuberculosis.